Global Political Economy - Ravenhill, John (New York Oxford University Press, 2017)
"This new edited textbook brings together leading international experts to provide an authoritative introduction to the major subject areas on undergraduate courses in global political economy. It is a 'stand-alone' textbook that deals with central themes and issues as well as outlining different theoretical approaches and engaging with contemporary debates such as global trade and production, global finance and the consequences of globalization. It is divided by subject areas into 4 sections for ease of navigation, and then sub-divided into chapters, each of which has been specifically written for this book. Carefully edited by John Ravenhill, the text reads as an integrated whole and is suitable as an introductory text for undergraduates in both coverage and approach, each chapter making full use of learning aids such as boxes to summarize key terms and debates, chronologies, case studies, web links and further reading, which complement the lively presentation of the subject"--Publisher description.
Include Glossary,References and Index
Keywords: Globalization -- Economic Aspects -- International Economic Relations -- International finance